What explains international interest rate co-movement? - Annika Camehl; Gregor von Schweinitz (Halle Institute for Economic Research (IWH), 2023)
We show that global supply and demand shocks are important drivers of interest rate co-movement across seven advanced economies. Beyond that, local structural shocks transmit internationally via aggregate demand channels, and central banks react predominantly to domestic macroeconomic developments: unexpected monetary policy tightening decreases most foreign interest rates, while expansionary local supply and demand shocks increase them. To disentangle determinants of international interest rate co-movement, we use a Bayesian structural panel vector autoregressive model accounting for latent global supply and demand shocks. We identify country-specific structural shocks via informative prior distributions based on a standard theoretical multi-country open economy model.
Keywords: C11; C30; E52; F42; 330; informative priors; panel vector autoregressions; spillovers; structural vector autoregressions